2008
DOI: 10.1016/j.tox.2008.07.048
|View full text |Cite
|
Sign up to set email alerts
|

Cell death and autophagy: Cytokines, drugs, and nutritional factors

Abstract: Cells may use multiple pathways to commit suicide. In certain contexts, dying cells generate large amounts of autophagic vacuoles and clear large proportions of their cytoplasm, before they finally die, as exemplified by the treatment of human mammary carcinoma cells with the anti-estrogen tamoxifen (TAM, <= 1 mu M). Protein analysis during autophagic cell death revealed distinct proteins of the nuclear fraction including CST-pi and some proteasomal subunit constituents to be affected during autophagic cell de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
90
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(96 citation statements)
references
References 76 publications
4
90
0
2
Order By: Relevance
“…Necrosis and apoptosis play a great role in the process (Bacon and Harris 2004;Kulkarni et al 2007;Bursch et al 2008). Blocking the necrosis and apoptosis process induced by hypoxia may help to slow down or even prevent the occurrence and progression of the injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Necrosis and apoptosis play a great role in the process (Bacon and Harris 2004;Kulkarni et al 2007;Bursch et al 2008). Blocking the necrosis and apoptosis process induced by hypoxia may help to slow down or even prevent the occurrence and progression of the injuries.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in cell proliferation is often coupled with an increase in cell death (Herrup and Busser, 1995;Ross, 1996), yet lack of nutrients can also induce cell death (Bursch et al, 2008;Franek, 1995). To test whether NR or DF induced cell death, we counted the number of dying cells in the tectum using SytoxO labeling (Faulkner et al, 2015) in the three nutrition treatment groups.…”
Section: Nutrient Availability Does Not Affect Cell Deathmentioning
confidence: 99%
“…Usually caspase 3 exists as an inactive 32kD zymogen in cytoplasma, also known as pro-caspase 3. After activated in early apoptotic process, it leads to limited proteolysis events and then the destruction of the cell (Grutter 2000;Bursch 2008). It has been found that caspase 3 can be regulated by several inhibitor of apoptosis proteins (IAPs), in which survivin is the smallest yet strongest anti-apoptotic member (Kanwar et al, 2012;McKenzie and Grossman, 2012;Zhang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%